A Phenomenological Study of Covid-19 Survivors Access to Healthcare - Mergal, Beryl Ben C.; Mendoza, Doris A. (8ISC Abstract Proceedings, 2022)
The aim of this phenomenological study was to investigate COVID-19 survivors’ experience in accessing health. The informants were chosen using criterion sampling, which involves a collection of predetermined inclusion and exclusion criteria. The researchers utilized an interview guide to help the informants articulate their lived experiences, challenges, coping strategies, and observed changes in their daily lives. The data collected was then transcribed, analyzed, interpreted, discussed, and broken down into themes that arose throughout the study. The analysis of the data gathered was facilitated with the use of the qualitative software NVIVO. The emerging themes on healthcare accessibility were easy access, lack of nurses, embarrassment, not being allowed to see loved ones , and hospitals’ failure to admit COVID-19 patients . These aforementioned emerging themes can be a part of the pillars of success in improving COVID-19 response and management in the current and future times. Keywords : covid-19 survivor, covid-19, phenomenological study, healthcare access